2004
DOI: 10.1016/j.ejheart.2003.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Acute hypoxic hepatitis (‘liver shock’): still a frequently overlooked cardiological diagnosis

Abstract: The diagnosis of acute hypoxic hepatitis remains problematic. We describe a series of 14 patients who were initially hospitalized in an hepatic care unit with a diagnosis of fulminant hepatitis, and were subsequently found to have acute hypoxic hepatitis ('liver shock') secondary to heart failure. A diagnostic algorithm is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 5 publications
1
34
0
Order By: Relevance
“…Denis et al reported good outcomes following treatment with diuretics, inotropes or vasodilators,(43) agents that support cardiac function and relieve elevated filling pressures. The use of such interventions is likely reserved for the sickest patients.…”
mentioning
confidence: 96%
“…Denis et al reported good outcomes following treatment with diuretics, inotropes or vasodilators,(43) agents that support cardiac function and relieve elevated filling pressures. The use of such interventions is likely reserved for the sickest patients.…”
mentioning
confidence: 96%
“…Moreover, certain imaging findings may add incremental value to IH diagnostic in difficult cases such as dilation of hepatic veins and inferior vena cava (23). Liver ultrasound might reveal hepatic changes, e.g., liver masses, which are accompanied by elevated levels of aminotransferase or other enzymes.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Congestive hepatopathy may be missed in patients with heart failure and mild hepatic congestion, and in patients with overt hepatic congestion and vague cardiac symptoms [174,175] . Physicians should consider right-sided heart failure in patients with hepatomegaly with or without jaundice.…”
Section: Diagnosismentioning
confidence: 99%